2014
DOI: 10.1111/gtc.12152
|View full text |Cite
|
Sign up to set email alerts
|

Schizosaccharomyces pombe centromere protein Mis19 links Mis16 and Mis18 to recruit CENP‐A through interacting with NMD factors and the SWI/SNF complex

Abstract: Japan CENP-A is a centromere-specific variant of histone H3 that is required for accurate chromosome segregation. The fission yeast Schizosaccharomyces pombe and mammalian Mis16 and Mis18 form a complex essential for CENP-A recruitment to centromeres. It is unclear, however, how the Mis16-Mis18 complex achieves this function. Here, we identified, by mass spectrometry, novel fission yeast centromere proteins Mis19 and Mis20 that directly interact with Mis16 and Mis18. Like Mis18, Mis19 and Mis20 are localized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 56 publications
6
60
0
Order By: Relevance
“…The kis1-1 mutant gene has a single missense mutation (corresponding to substitution of arginine 65 to cysteine), which lies between the coiled-coil regions ( Figure 4C ). Although no homologous proteins were curated in PomBase, closely related yeast species had orthologs, e.g., SPOG_04358 of Schizosaccharomyces cryophilus , SOCG_03381 of Schizosaccharomyces octosporus , and SJAG_03510 of Schizosaccharomyces japonicus ( Figure 4D ), as noted previously [68], [69]. We also realized that the budding yeast S. cerevisiae appears to have a homologous protein (YOR231C-A), although it is a putative protein and sequence similarity is seen only in limited regions ( Figure 4D ).…”
Section: Resultssupporting
confidence: 67%
“…The kis1-1 mutant gene has a single missense mutation (corresponding to substitution of arginine 65 to cysteine), which lies between the coiled-coil regions ( Figure 4C ). Although no homologous proteins were curated in PomBase, closely related yeast species had orthologs, e.g., SPOG_04358 of Schizosaccharomyces cryophilus , SOCG_03381 of Schizosaccharomyces octosporus , and SJAG_03510 of Schizosaccharomyces japonicus ( Figure 4D ), as noted previously [68], [69]. We also realized that the budding yeast S. cerevisiae appears to have a homologous protein (YOR231C-A), although it is a putative protein and sequence similarity is seen only in limited regions ( Figure 4D ).…”
Section: Resultssupporting
confidence: 67%
“…Mis18 must play a critical role in this process. Recently, three groups have identified a new component of the Mis18 complex in fission yeast, named Eic1 (also known as Mis19), and they have shown that Eic1, together with Mis16 and Mis18, plays an essential role in CENP-A Cnp1 recruitment [32,33,40]. It would be interesting to explore how these three components of the Mis18 complex associate and coordinate with each other for successful CENP-A Cnp1 recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…The Mis18 complex is composed of Mis16, Mis18, and Eic1 in fission yeast and Mis18α, Mis18β, M18BP1, and RbAp46/48 in human [27,30,32,33]. Temperature-sensitive (ts) mutations of Mis16 and Mis18 in fission yeast impair proper CENP-A localization and chromosome segregation at non-permissive temperatures [27].…”
Section: Introductionmentioning
confidence: 99%
“…To obtain ts mutants of the sam1 + gene, we employed a PCR-based random mutagenesis screen (Hayashi et al., 2014b) (Figure S1). The sam1 DNA fragment, in which the hygromycin-resistance-encoding marker gene, hph , was inserted just downstream of the stop codon of the sam1 + gene open reading frame, was amplified by PCR under error-prone conditions, containing increased MgCl 2 (Eckert and Kunkel, 1990).…”
Section: Resultsmentioning
confidence: 99%